Let f ( x ) = x 2 + 6 x + 6 f ( x ) = x 2 + 6 x + 6 , and g ( x ) = 1 g ( x ) = 1 . Find all values for the variable x x , for which f ( x ) = g ( x ) f ( x ) = g ( x ) .

Respuesta :

Answer:

Therefore the value of x are = -1 and -5 for which f(x)=g(x).

Step-by-step explanation:

Given,

f(x)=x²+6x+6    and    g(x)=1

f(x)=g(x)

⇒x²+6x+6=1

⇒x²+6x+6-1=0

⇒x²+6x+5=0

⇒x²+5x+x+5=0

⇒x(x+5)+1(x+5)=0

⇒(x+5)(x+1)=0

⇒x+5=0     or       x+1=0

⇒x=-5                     x=-1

Therefore the value of x are = -1 and -5.

ACCESS MORE